2010
DOI: 10.1111/j.1748-3743.2009.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clear visual input and change in standing sequence on standing sway related to falls during night toilet use

Abstract: It is important for nurses to train older patients to turn on the light and perform standing pattern B, when going to the bathroom at night. In addition, it is advisable to confirm the placement of distinct visual markers on the way to the bathroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Velde et al [13] reported that by decreasing or stopping hypnotics, which are thought to be one of the FRID, they morning [8][9][10]. The hypnotic effects that are seen when excreting at night or early in the morning may affect falls.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Velde et al [13] reported that by decreasing or stopping hypnotics, which are thought to be one of the FRID, they morning [8][9][10]. The hypnotic effects that are seen when excreting at night or early in the morning may affect falls.…”
Section: Discussionmentioning
confidence: 95%
“…In alertness, the results of rilmazafone were significantly worse than those of the triazolam (p<0.05). (1) Sleep quality Good (11), bad (2) Well being Good (4), not bad (4), fair (9), not good (0), bad (1) …”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Annual age-induced motor function decline may be observed (8)(9)(10); therefore, the time staying in the toilet may be prolonged by the deterioration of voiding behaviors. When motor function deteriorates due to paralysis or muscle weakness, older adults easily lose truncal balance when wearing and removing underwear and clothes, cleaning the buttocks, and standing from the toilet seat (11)(12)(13). This functional deterioration may gradually manifest as difficulties in performing repeated joint movements, such as dressing and standing.…”
Section: Resultsmentioning
confidence: 99%